2012
DOI: 10.1002/j.1532-2149.2012.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of trigeminal ganglionic Nav1.7 in hyperalgesia of inflamed temporomandibular joint is dependent on ERK1/2 phosphorylation of glial cells in rats

Abstract: Trigeminal ganglionic Nav 1.7 has an important function in the hyperalgesia of the inflamed TMJ, which is dependent on the communication with the satellite glials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…In addition, the nociceptor-specific knockout of Nav1.7 [19] and the knock-down of Nav1.7 [20] in primary afferents abrogate inflammatory hyperalgesia. Our previous study also found trigeminal ganglionic Nav1.7 is involved in hyperalgesia of inflamed TMJ [22]. These findings strongly suggest that Na v 1.7 plays an important role in pain.…”
Section: Evaluation Of the Hypothesissupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, the nociceptor-specific knockout of Nav1.7 [19] and the knock-down of Nav1.7 [20] in primary afferents abrogate inflammatory hyperalgesia. Our previous study also found trigeminal ganglionic Nav1.7 is involved in hyperalgesia of inflamed TMJ [22]. These findings strongly suggest that Na v 1.7 plays an important role in pain.…”
Section: Evaluation Of the Hypothesissupporting
confidence: 54%
“…A nucleotide polymorphism in Nav1.7 alters pain perception in patients with either knee or hip osteoarthritis [21]. Furthermore, our previous study also showed that trigeminal ganglionic Nav1.7 was involved in hyperalgesia of inflamed TMJ [22].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The increase in the amplitude of vibrations damages the permeability of ion channels, leading to nerve injury. The disorder is characterized by recurrent, paroxysmal attacks of sudden, intense, and piercing pain within the region supplied by the trigeminal nerve, comparable to an electric shock [5–7, 9–19, 30]. …”
Section: Trigeminal Neuralgiamentioning
confidence: 99%
“…Neuralgia of this type may be a symptom of numerous diseases within the region of the posterior cranial fossa, such as basal tumors or cerebellopontine angle tumors. This type of neuralgia may also be observed in alcohol, mercury, or nicotine intoxication [8–13, 15, 18, 30]. …”
Section: Trigeminal Neuralgiamentioning
confidence: 99%